Analysis Use Motivation Study Student in Islamic Religious Education Learning Using the PAKEM Method in Senior High Schools - Batula, Abu Warasy; Faqihuddin, Achmad; Munandar, Haris; Zakaria (Medina-te : Jurnal Studi Islam, 2024)
This study analyzes the effectiveness of the PAKEM method (Active, Creative, Effective, and Enjoyable Learning) in improving students' learning motivation in Islamic Religious Education (PAI) learning among high school students in Bandung. The method used in this study is quantitative with a cross-sectional survey design and data collection techniques using a Likert scale questionnaire instrument totaling 21 items. Each question item has been tested for validity and reliability and has a size greater than the r table value (0.325) with a significance level of 5%. Learning motivation is examined through four aspects: relationship, satisfaction, attention, and self-confidence developed based on Keller's theory. The findings of the study showed high overall motivation aspects, with a total score of 78.24%. Relationship is the aspect with the highest score, indicating students' perceptions of the practical value of PAI in their lives, followed by satisfaction, reflecting the success of the method in creating a positive and satisfying learning experience. The level of attention is maintained through interactive and varied learning activities, while self-confidence, although rated the lowest, is still high, indicating further opportunities to foster self-confidence among students. This study concludes that the engaging PAKEM approach effectively increases motivation and supports cognitive engagement in religious studies, recommending continued implementation with a focus on enhancing student confidence through additional structured speaking and presentation practice.